The Ligurian High-School Educational Project on Palliative Care: Development and Piloting of a School-Based Intervention on Bereavement and Severe Illness. (November 2014) - Beccaro, Monica; Gollo, Giorgia; Giordano, Monica; Igazzini, Jessica; Servente, Valentina; Vignali, Stefano; Costantini, Massimo; Leo, Silvia Di
This study was aimed at developing and piloting a school-based intervention on severe illness-induced bereavement through a project focused on spreading knowledge of palliative care among high school students (phases 0-II Medical Research Council Framework). The intervention entailed the screening of a topic-related movie and a classroom meeting. Eight classes from 2 high schools participated, and a before–after evaluation was used to assess intervention feasibility and impact. Valid questionnaires, including 2 open-ended questions focusing on bereavement and strategies for coping with loss, were filled in by 89% (before) and 84% (after) of the 159 students. In the after evaluation, content analysis on the "strategies" question showed that answers concerning closeness and sharing were reported more frequently. Positive feedback was collected as regards the overall experience.